2016
DOI: 10.1016/j.molmed.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection: Pathogenesis and Outlook

Abstract: The clinical syndromes comprising urinary tract infection (UTI) continue to exert significant impact on millions of patients worldwide, most of whom are otherwise healthy women. Antibiotic therapy for acute cystitis does not prevent recurrences, which plague up to one fourth of women after an initial UTI. Rising antimicrobial resistance among uropathogenic bacteria further complicates therapeutic decisions, necessitating new approaches based on fundamental biological investigation. In this review, we highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
235
0
33

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(271 citation statements)
references
References 118 publications
3
235
0
33
Order By: Relevance
“…During DSE, the chaperone's donor strand is replaced by the N-terminal extension (Nte) of the next subunit in assembly. Subunit's Ntes are [10][11][12][13][14][15][16][17][18][19][20] residue N-terminal sequences found in each subunit except for the tip adhesin. After DSE, the Nte provides the donor-strand for the previously assembled subunit, engaging the P1 to P5 pockets of the previously assembled subunit's groove via its corresponding P1 to P5 residues 20,23 .…”
Section: Cu Pilus Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…During DSE, the chaperone's donor strand is replaced by the N-terminal extension (Nte) of the next subunit in assembly. Subunit's Ntes are [10][11][12][13][14][15][16][17][18][19][20] residue N-terminal sequences found in each subunit except for the tip adhesin. After DSE, the Nte provides the donor-strand for the previously assembled subunit, engaging the P1 to P5 pockets of the previously assembled subunit's groove via its corresponding P1 to P5 residues 20,23 .…”
Section: Cu Pilus Biogenesismentioning
confidence: 99%
“…Escherichia coli (UPEC) has been particularly well documented 9,10 . UPEC elaborates two types of pili, type 1 and P pili 5 , which will be used here as paradigms to highlight the structure and assembly of surface organelles assembled by the CU pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Nearly 1/4 th of the UTI cases show recurrences in another study. [5] One more study done for evaluation of risk factors for and molecular characteristics of community-onset extended-spectrum cephalosporin-resistant (ESC-Enterobacteriaceae (EB) urinary tract infections (UTIs) in a US health system, showed that use of trimethoprim-sulfamethoxazole, diabetes, older age etc were associated with community-onset ESC-R EB UTI. [27] Thus, this problem of antibiotic resistance among the members of enterobacteriaceae including E.coli is prevalent in many developing and developed countries.…”
Section: World Journal Of Pharmaceutical Researchmentioning
confidence: 99%
“…UTI exerts its impact in the form of clinical syndrome over millions of patients in the world effecting mostly women who are healthy otherwise. [5] UTI occurs mainly due to invasion of the bladder, urethra or kidneys by pathogens. [6] Uropathogenic E.…”
Section: Introductionmentioning
confidence: 99%
“…Uropathogenic strains of Escherichia coli (UPEC) are by far the most common etiological agent of UTI, causing severe bladder infection (cystitis) and acute kidney infections (pyelonephritis). 1 UTI onset frequently involves an underlying dysfunction of host defenses, including pathogen recognition and antimicrobial factors, coupled with effective pathogen-specific virulence properties of invasiveness and immune resistance.…”
Section: Introductionmentioning
confidence: 99%